Mesolithic of the Eastern Fennoscandia: chronology and periodization - Dmitriy V. Gerasimov (Археология евразийских степей)
Basing on the array of radiocarbon dates got over the last decades the chronological framework of the Mesolithic of Eastern Fennoscandia was determined from the beginning of the Ancylus (8900 BC) to the maximum of the Litorina (5500 BC) transgressions of the Ancient Baltic Sea region. Periods of the Early and the Late Mesolithic can be confidently distinguished. These periods differ significantly in terms of material culture, settling, subsistence strategy and interregional communication systems. Although the differences between the "initial" and "final" appearance of culture are very significant, judging by the available data, the changes accumulated gradually. It is proposed to consider the climatic event "9300 cal. BP" as the conditional boundary line between these periods. The climatic event "8200 cal. BP" could probably be the cause of social and cultural stress for the population of the Eastern Fennoscandia, but did not lead to archaeologically visible cultural transformations.